Yangian of the Strange Lie Superalgebra of Qn₋₁ Type, Drinfel'd Approach - Stukopin, V. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
The Yangian of the strange Lie superalgebras in Drinfel'd realization is defined. The current system generators and defining relations are described.